Nitrogen-containing furanose and pyranose analogues from Hyacinthus orientalis. - Asano, N; Kato, A; Miyauchi, M; Kizu, H; Kameda, Y; Watson, A; Nash, R; Fleet, G (1998)
Aqueous methanol extracts from the bulbs of Hyacinthusorientalis were subjected to various ion-exchange column chromatographic steps to give 2(R),5(R)-bis(hydroxymethyl)-3(R),4(R)-dihydroxypyrrolidine (DMDP) (1), 2,5-dideoxy-2,5-imino-dl-glycero-d-manno-heptitol (homoDMDP) (2), 2,5-imino-2,5,6-trideoxy-d-manno-heptitol (6-deoxy-homoDMDP) (3), 2,5-imino-2,5,6-trideoxy-d-gulo-heptitol (4), 1-deoxynojirimycin (5), 1-deoxymannojirimycin (6), alpha-homonojirimycin (7), beta-homonojirimycin (8), alpha-homomannojirimycin (9), beta-homomannojirimycin (10), and 7-O-beta-d-glucopyranosyl-alpha-homonojirimycin (MDL 25,637) (11). The structures of the new natural products 3 and 4 were determined by spectroscopic analysis, including extensive 1D and 2D NMR studies. Compound 2 was found to be a potent inhibitor of bacterial beta-glucosidase, mammalian beta-galactosidases, and mammalian trehalases, while 3 was a potent inhibitor of rice alpha-glucosidase and rat intestinal maltase. Compound 4 was observed to be a good inhibitor of alpha-l-fucosidase.